The Shape of Stories : Narrative Structures in Cuneiform Literature - Helle, Sophus,; Konstantopoulos, Gina, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
How were narratives composed in the ancient Near East? What patterns and principles, constraints and considerations guided the shaping of cuneiform stories? The study of narrative structures has emerged as a promising approach to the textual heritage of the cuneiform world. Engaging with practically any ancient text - whether literary, historical, or religious - requires some understanding of the narrative forms that shaped their content. This volume gives researchers the tools to better understand those form, illustrating each approach to narrative analysis with a case study from the cultures of the ancient Near East: Sumerian, Babylonian, Assyrian, and Hittite. .